Respectful maternity care and mistreatment: Women’s experiences during induction of labor and childbirth in Ghana - Kwame Adu-Bonsaffoh; Grace T. Newman; Kenneth Atobrah-Apraku; Yaw Opuni-Frimpong; Joseph D. Seffah (PLoS ONE, 2025)
Background Most studies on respectful maternity care (RMC) and mistreatment of women have focused on intrapartum care with limited information on how women are treated during induction of labor (IOL), pre-labor phase of the maternity care continuum. Emerging multi-country evidence indicates that nearly 30% of women who undergo IOL do not consent to the procedure and constitutes a violation of their rights to optimal maternal health. This study explored women’s lived experiences of respectful care and mistreatment during IOL in a tertiary setting in Ghana. Methods This was a qualitative phenomenological study conducted between September 2021 to October 2021 in Ghana. The eligibility criteria comprised women, aged ≥ 18 years who underwent IOL with singleton gestations. Purposive sampling was employed in recruiting the study participants (n = 17). Data analysis was performed based on thematic content using the inductive qualitative analytic framework approach. Results Nearly all the participants (94.1%) were first-timers to IOL. In general, we determined mixed findings relating to the experiences of RMC (respectful versus disrespectful care). Some women experienced respectful care including effective communication, optimal counseling and appropriate professionalism resulting in adequate client satisfaction with care. Conversely, we determined that some mothers experienced mistreatment of different types during labor induction and birth including verbal abuse, lack of privacy, neglect, ineffective communication, inadequate pain relief, non-consented care and inadequate professional standards. There were no reports of physical abuse. Mixed responses (positive and negative) were heartily described concerning future utilization of the health facility considering the quality of care they received. Personalized recommendations to improve the quality of care during IOL were provided by the affected women and these summed up to RMC (e.g. effective communication, adequate analgesia, shared-decision making). Conclusion Our study indicates that women experience varied forms of mistreatment during induction of labor and childbirth, and can be potentially traumatic psychologically considering their prolonged exposure to health facilities. Context specific strategies to expedite integration and adherence to RMC guidelines in maternity care are recommended to improve the quality of care during induction of labor and birth.